ANALYSIS OF THE VALUES OF RELIGIOUS TOLERANCE CONTAINED IN THE GOVERNMENT INTEGRATED THEMATIC COMPANY BOOK IN THE FRAMEWORK OF CIVIC EDUCATION LEARNING - Pepsi Febriyanti; Sindi Prasetyani (2022)
This research analyzes the value of religious tolerance contained in an integrated thematic companion book for grade 2 within the scope of Civics Education learning based on Tillman D (2004) in Values Education for Young Adults. Risa Pratono's translation). Jakarta: Grasindo. This study uses a descriptive qualitative method with the instrument in the form of documentation. The data source used is a document: